Menneiden ja tulevien äänten risteyksessä - Grönholm Pertti (My University, 2022)
In Finnish popular music, the adoption of electronic musical instruments, such as synthesizers, drum machines, sequencers, samplers, computers and musical software progressed slowly and was a complicated process until the early 1990s. Compared with Swedish, German and British pop and rock the electronic instruments remained longer in the margins of rock and pop rock. Regardless of the breakthrough of synths and drum machines in certain styles, such as progressive rock, funk and disco, synth pop and hip hop, the majority of Finnish bands and artists shunned synthesizers until the mid-1980s. Only after the waves of hip hop, house, techno and euro dance in the late 1980s and early 1990s, synthesizers were widely accepted as ‘normal’ and equal rock instruments.
In this article, I focus on the adoption of music technology among Finnish rock and pop musicians of the 1970s and 1980s. I have interviewed three electronic musicians from three different generations. Esa Kotilainen (b. 1946), Pekka Tolonen (b.1957) and Tommi Lindell (b.1966) have all witnessed several turns in the emergence of electronic musical instruments. They have also experienced various changes in lieu the accessibility and acceptability of synthesizers. In Finland, they are known as the early adopters and intensive users of the musical electronics.
In the first section of the article I ask, when and how electronic musical instruments became more popular in Finland and how they were adopted and used in progressive rock, new wave, synth pop, goth rock and mainstream pop. I also frame an overview on the adoption of synthesizers in Finnish pop and rock. The section also parallels the developments with Finnish schlager and disco, where synthesizers were intensively used by a handful of composers and producers in the late 1970s and early 1980s. In this section, I primarily utilized published interviews and magazine articles supplemented with a small selection of musical release reviews and synthesizer advertisements.
The next three sections follow my observations and conclusions which primarily stem from the interviews with three above-mentioned musicians. I also utilize some additional interviews with other musicians. I inquired how the interviewees encountered electronic instruments, how they have used their instruments and how the early adoption of synthesizers has contributed to their understanding of sound and music. Furthermore, we discussed on the impact of the electronic instruments on their musicianship, career and the regeneration of their professional image. Regarding the ‘synthesizer turns’ in the history of Finnish pop and rock I invited the interviewees to recall the response displayed by their fellow musicians, producers and the audience.
In the concluding section, I sum up my observations. One of them is that in Finland electronic musical instruments seem to gain in popularity in jumps which coincide not only with international pop trends but also with some major technological developments and the waves of marketing. This is not unexpected by any means, but it makes an interesting case in Finland. While the more advanced and more affordable synthesizers of the period 1980–83 marked the final breakthrough of electronic instruments in Western pop and rock, in Finland only a couple of tens of musicians adopted synthesizers as their primary instruments. Furthermore, in Finland only a handful of fully or almost fully electronic bands emerged in the early 1980s. All of them remained short-lived. Only some of the most popular teeny pop bands of the early and mid-1980s adopted synthesizers as their main keyboards.
The accelerated marketing cycles of synthesizers provoked suspicion among some Finnish musicians; synthesizers could be left aside as novelty gimmicks and earmarks of a momentary trend. One reason for denouncing the ‘synths’ in the 1980s mainstream rock may have been the developing ‘Suomi-rock’ (Finnish rock), a down-to-earth, nationally and locally rooted style which got a heavy dose of influence from Finnish folk and the long tradition of Finnish schlager. One extra reason for a rocker in keeping off synthesizers was the extensive use of electronic musical instruments in Finnish light pop and schlager in the early 1980s. However, in the late 1980s it became audible that synthesizers had survived and welcomed in the margins of rock, pop and especially within the emerging new styles of electronic dance music.
Avainsanat: musiikkiteknologia, syntetisaattorit, populaarimusiikki, musiikin historia